Alternative Oxidase (AOX) Genes of African Trypanosomes: Phylogeny and Evolution of AOX and Plastid Terminal Oxidase families - Suzuki, T.; Hashimoto, T.; Yabu, Y.; Majiwa, Phelix A.O.; Ohshima, S.; Suzuki, M.; Lu, S.; Hato, M.; Kido, Y.; Sakamoto, K.; Nakamura, K.; Kita, K.; et al. (Wiley, 2005)
To clarify evolution and phylogenetic relationships of trypanosome alternative oxidase (AOX) molecules, AOX genes (cDNAs) of the African trypanosomes, Trypanosoma congolense and Trypanosoma evansi, were cloned by PCR. Both AOXs possess conserved consensus motifs (-E-, -EXXH-). The putative amino acid sequence of the AOX of T. evansi was exactly the same as that of T. brucei. A protein phylogeny of trypanosome AOXs revealed that three genetically and pathogenically distinct strains of T. congolense are closely related to each other. When all known AOX sequences collected from current databases were analyzed, the common ancestor of these three Trypanosoma species shared a sister-group position to T. brucei/T. evansi. Monophyly of Trypanosoma spp. was clearly supported (100% bootstrap value) with Trypanosoma vivax placed at the most basal position of the Trypanosoma clade. Monophyly of other eukaryotic lineages, terrestrial plants + red algae, Metazoa, diatoms, Alveolata, oomycetes, green algae, and Fungi, was reconstructed in the best AOX tree obtained from maximum likelihood analysis, although some of these clades were not strongly supported. The terrestrial plants + red algae clade showed the closest affinity with an a-proteobacterium, Novosphingobium aromaticivorans, and the common ancestor of these lineages, was separated from other eukaryotes. Although the root of the AOX subtree was not clearly determined, subsequent phylogenetic analysis of the composite tree for AOX and plastid terminal oxidase (PTOX) demonstrated that PTOX and related cyanobacterial sequences are of a monophyletic origin and their common ancestor is linked to AOX sequences.